The genomic study of an environmental isolate os Scedosporium apiospermum shows its metabolic potential to degrade hydrocarbons (2017)
Crude oil contamination of soils and waters is a worldwide problem, which has been actively addressed in recent years. Sequencing genomes of microorganisms involved in the degradation of hydrocarbons have allowed the identification of several promoters, genes and degradation pathways of these contaminants, allowing a better understanding of the functional dynamics of microbial degradation. Here, we report a first draft ofthe 44.2 Mbp genome assembly of an environmental strain of the fungus Scedosporium apiospermum. The assembly consisted of 186 high-quality DNA scaffolds with 1.62 % of sequence repeats identified. A total of 11,195 protein-coding genes were predicted including a diverse group of gene families involved in hydrocarbon degradation pathways like dioxygenases and cytochrome P450 monooxygenases.